Compact Ku-band transmitter design for satellite communication applications : from system analysis to hardware implementation - Lee, Chang-Ho (Kluwer Academic Publishers, 2002)
Compact Ku-band Transmitter Design for Satellite Communication Applications reviews approaches to and topologies of Ku-band transmitters. The advantages and disadvantages of these transmitters are explored along with critical design criteria necessary to enhance system performance. The design and implementation of a functional compact LTCC-based transmitter module featuring an integrated filter and MMIC chipsets are explained. Through this book, the reader will learn to analyze, design and characterize these transceiver modules. Compact Ku-band Transmitter Design for Satellite Communication Applications's strength is clearly seen in its focus on component-based design for wireless system applications. This aspect represents realistic views of today's wireless design. The book will bring essential design skills to engineers as well as references to the academic community.